Determination of Factors Affecting Firm Value in Manufacturing Companies - Monica Pratiwi (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to explore the impact of leverage, profitability, company size, managerial ownership, and corporate social responsibility (CSR) on the value of a company. The population that is the focus of this study are 68 manufacturing companies listed on IDX during the 2019-2022 period. The method applied is purposive sampling. The results showed that leverage as well as profitability have a significant influence on firm value, while firm size, managerial ownership, and CSR do not have any significant influence on firm value.